Isolation, characterization and in vitro anti-salmonellal activity of compounds from stem bark extract of Canarium schweinfurthii - Jean Baptiste SOKOUDJOU; Olubunmi ATOLANI; Guy Sedar Singor NJATENG; Afsar KHAN; Cyrille Ngoufack TAGOUSOP; André Nehemie BITOMBO; Norbert KODJIO; Donatien GATSING (BMC, 2020)
Abstract Background Bacteria belonging to the Salmonella genus are major concern for health, as they are widely reported in many cases of food poisoning. The use of antibiotics remains a main stream control strategy for avian salmonellosis as well as typhoid and paratyphoid fevers in humans. Due to the growing awareness about drug resistance and toxicities, the use of antibiotics is being discouraged in many countries whilst advocating potent benign alternatives such as phyto-based medicine. The objective of this work was to isolate, characterise the bioactive compounds of Canarium schweinfurthii; and evaluate their anti-salmonellal activity. Methods The hydro-ethanolic extract of Canarium schweinfurthii was fractionated and tested for their anti-salmonellal activity. The most active fractions (i.e. chloroform and ethyl acetate partition fractions) were then explored for their phytochemical constituents. Fractionation on normal phase silica gel column chromatography and size exclusion chromatography on Sephadex LH-20 led to the isolation of four compounds (maniladiol, scopoletin, ethyl gallate and gallic acid) reported for the first time in Canarium schweinfurthii. Results Result indicated that scopoletin and gallic acid had greater activity than the crude extracts and partition fractions. Among the isolated compounds, scopoletin showed the highest inhibitory activity with a MIC of 16 μg/ml against Salmonella Typhimurium and Salmonella Enteritidis. Conclusions The overall results of this study indicates that the hydro-ethanolic extract as well as some of isolated compounds have interesting anti-salmonellal activities that could be further explored for the development of potent therapy for salmonellosis. Furthermore, the study adds credence to the folkloric applications of the plant.